Retrospective clinical features and renal pathological analysis of 15 children with anti-neutrophil cytoplasmic antibody-associated vasculitis - Guan, Na (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2013)
OBJECTIVE: Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis is a disorder with poor prognosis. This study aimed to improve the diagnosis and treatment of ANCA associated vasculitis of children, to analyze the clinical features, pathological characteristics and the prognosis of children with ANCA-associated vasculitis